The autoignition of iso-dodecane in low to high temperature range: An experimental and modeling study - Mao, Yebing; Feng, Yuan; Wu, Zhiyong; Wang, Sixu; Yu, Liang; Raza, Mohsin; Qian, Yong; Lu, Xingcai (Combustion and flame, 2019)
2,2,4,6,6-pentamethylheptane, a highly branched alkane, is a promising component candidate of branched alkanes in the surrogates for jet fuels and a major component in alternative fuels. In spite of its great relevance and importance in real fuels, it has only attracted very little interest. This work provides a new set of experimental data and a newly proposed detailed kinetic mechanism for this hydrocarbon. In the experiments, the autoignition characteristics of 2,2,4,6,6-pentamethylheptane, was measured in a rapid compression machine and a shock tube spanning over the equivalence ratios of 0.5, 1 and 1.5, pressures of 15 and 20 bar and temperature range of 603–1376 K. The dependence of ignition delay times on pressure, mole fraction of fuel, mole fraction of oxygen and dilution ratio were systematically investigated. Negative temperature coefficient (NTC) behavior was observed during the autoignition event, but the NTC temperature window was found to be much lower than the counterpart normal paraffin. A detailed kinetic model containing 729 species and 3390 reactions was proposed to describe the combustion behavior of this compound over low-to-high temperature range. The model was validated against the present experimental data, as well as the limited datasets in literature. Good agreements were observed between the experimental data and the predictions from the proposed model. Kinetic analyses, including sensitivity analysis and reaction pathway analysis, were carried out to provide insight into the combustion characteristics from the kinetic perspective. Comparisons were also carried out with the datasets for other branched alkanes and normal-paraffin with same carbon numbers over the same conditions to reveal the effects of the molecular structure.